Development of Malay Deli Songket Motifs Based on Symmetry Groups - Mingka, Rizka Annisa; Kartika, Dinda; Suwanto, Fevi Rahmawati (JTAM (Jurnal Teori dan Aplikasi Matematika), 2023)
One of the tribes in North Sumatra Province that has a wide variety of art is the Deli Malays, especially the Songket motifs. Songket is a type of traditional Indonesian weaving that should be preserved to maintain Indonesia’s wealth. The motifs in the Malay Deli Songket can be analyzed because of its symmetrical pattern. In this study, the author developed the Malay Deli Songket motif based on the concept of the symmetry group. The motif development was carried out with the Matlab program based on the frieze group pattern and the crystallography group pattern. The Frieze pattern, often called the Frieze Group, is a symmetry group created from one-way translation, forming a linear pattern that repeats one way. The crystallography group has 17 crystallographic patterns formed by a specific transformation from each type of unit lattice. Through the development of motifs, 6 new Songket motifs were obtained based on the Frieze pattern in 11 observed Malay Deli Songket motifs, namely the Moon Orchid motif, the Orchid motif, the Balong Ayam motif, the Coffee Flowers motif, the Tobacco Leaves 1 and 2 motifs, the Corn motif, the Paddy motif, the Tampuk Manggis motif, the Tobacco motif, and the Ulam Raja motif. In 4 previously observed Malay Deli Songket motifs, 11 new Songket motifs were obtained for crystallography patterns: the Deli Tobacco Leaves motif, the Coffee motif, the Tampuk Gelugor motif, and the Undang Kupu-Kupu motif.